THE NEW EDITION OF THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN – THE LEGAL BASIS FOR THE DEVELOPMENT OF THE COUNTRY - Naim Oblomurodov (Western European Studies, 2024)
the article describes the adoption of the new edition of the Constitution of New Uzbekistan, which came into force on May 1, 2023, and its main content, which is an important basis for ensuring human rights and freedoms, as well as the issues of declaring Uzbekistan as a “social state.” It also covers the principles of increasing the countryʻs prestige in the world community, increasing its position and prestige as an equal subject of international relations, the organization of state power and management processes, ecology, attention to family and other issues.
Keywords: Uzbekistan; Constitution; person